Case Study on the Spatial Development Impact Assessment Tool Applied in the Spatial Development Environmental Security Assessment - David Rehak; Pavel Hrdina; Michail Senovsky; Jiri Dvorak (Communications - Scientific letters of the University of Zilina, 2011)
The paper deals with the spatial development environmental security assessment employing the Spatial Development Impact Assessment tool and the geographical information systems. The first part includes a more detailed description of the Spatial Development Impact Assessment tool and ESRI – ArcInfo, which were the basis for elaborating the case study. The case study is presented in the second part of the paper, which includes the spatial development environmental security assessment for a fictitious hazardous waste incineration plant located in the zone of Moravian-Silesian region of the Czech Republic. The acquired outcomes are presented in the final part of the paper together with the proposed measures to be taken in order to reduce the potential risk of intended spatial development.